2011
DOI: 10.1002/cmdc.201100317
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Discovery of Allosteric Modulators of Two Related Class B G‐Protein‐Coupled Receptors

Abstract: Despite the availability of X-ray crystal structure data for several members of the G-protein-coupled receptor (GPCR) superfamily, structure-based discovery of GPCR ligands has been exclusively restricted to class A (rhodopsin-like) receptors. Herein we report the identification, by a docking-based virtual screening approach, of noncompetitive ligands for two related class B (secretin-like) GPCRs: the glucagon receptor (GLR) and the glucagon-like peptide 1 receptor (GLP-1R). Starting from a knowledge-based thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 82 publications
4
87
0
Order By: Relevance
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 90%
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 90%
“…Discovery of allosteric compounds is considered a much more challenging problem, with only a few examples of putative allosteric hits arising from VLS campaigns (de Graaf et al, 2011b;Mysinger et al, 2012). In this study, we specifically aimed at expanding large-scale VLS applications beyond orthosteric sites by 1) developing an optimized D3R APO model of the full binding pocket with allosteric extension, and 2) developing an ND, no inhibition of 10 nM dopamine detected.…”
Section: Discussionmentioning
confidence: 99%
“…The successful three dimensional (3D) structure characterization through crystallography of ADRB2 bound to its antagonist carazolol (Cherezov et al, 2007) was followed by 3D characterization of some other GPCRs Jaakola et al, 2008;Shimamura et al, 2011;Wacker et al, 2010;Wu et al, 2010), which have offered opportunities to construct, validate and perform SBVS to discover novel potent ligands for a particular GPCR both on the crystal structures (Carlsson et al, 2010;Katritch et al, 2010;Kolb et al, 2009;Yakar and Akten, 2014) and homology models (Carlsson et al, 2011;de Graaf et al, 2011 b ;Istyastono et al, 2011 b ;Sirci et al, 2012;Tarcsay et al, 2013). Solely used of SBVS approaches on Histamine H1 Receptor (HRH1) crystal structure in the recent virtual screening campaigns showed extraordinary results, both retrospectively and prospectively .…”
Section: Introductionmentioning
confidence: 99%